2007
DOI: 10.1673/031.007.1501
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Release Rates on the Effectiveness of Augmentative Biological Control Agents

Abstract: To access the effect of augmentative biological control agents, 31 articles were reviewed that investigated the impact of release rates of 35 augmentative biological control agents on the control of 42 arthropod pests. In 64% of the cases, the release rate of the biological control agent did not significantly affect the density or mortality of the pest insect. Results where similar when parasitoidsor predators were utilized as the natural enemy. Within any order of natural enemy, there were more cases where re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 40 publications
1
29
0
4
Order By: Relevance
“…Under these conditions, the efficacy of both low and high release rates is quite unsatisfactory and we did not detect a significant increase in the parasitism rate. The limited effect of the high release rate found in our plots agrees with the revision paper published by Crowder (), who reported that of 19 crop pests, in the 63% of the cases increasing the release rate of parasitoids did not affect the density, mortality or parasitism rate of the herbivores. To achieve a higher protection of the stands from G. platensis attack, a release of A. nitens by massive inundation could be the better strategy, but a more appropriate approach may be to limit eucalypt plantations to low altitude areas where natural biological control is satisfactory (Cordero Rivera et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Under these conditions, the efficacy of both low and high release rates is quite unsatisfactory and we did not detect a significant increase in the parasitism rate. The limited effect of the high release rate found in our plots agrees with the revision paper published by Crowder (), who reported that of 19 crop pests, in the 63% of the cases increasing the release rate of parasitoids did not affect the density, mortality or parasitism rate of the herbivores. To achieve a higher protection of the stands from G. platensis attack, a release of A. nitens by massive inundation could be the better strategy, but a more appropriate approach may be to limit eucalypt plantations to low altitude areas where natural biological control is satisfactory (Cordero Rivera et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…modify the control capacity of a natural enemy (Collier & van Steenwyk, 2004;Stiling & Cornelissen, 2005;Crowder, 2006;Desneux et al, 2007). Nesidiocoris tenuis was released 5 days before transplanting and the first whitefly release was carried out just after transplanting (week 0).…”
Section: Figurementioning
confidence: 99%
“…Within Scymninae, the genera Zilus Mulsant (Scymnillini) and Nephaspis Casey (Scymnini) also feed primarily on whiteflies (Gordon, 1985(Gordon, , 1994. Nephaspis oculatus (Blatchley) is another important predator of Bemisia whiteflies (Liu and Stansly, 1996;Crowder, 2006).…”
Section: Food Preferencementioning
confidence: 99%